Teaching Factory Engagement, Entrepreneurial Knowledge, Social Relationships, and Vocational Students' Entrepreneurial Mindset - Widoretno, Yustin Setiya; Marji, Marji; Tuwoso, Tuwoso; Kuncoro, Tri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study examined the relationships among student engagement in the Teaching Factory (TEFA), entrepreneurial knowledge, social relationships, self-efficacy, and entrepreneurial mindset among vocational high school students in East Java, Indonesia. A quantitative, cross-sectional ex post facto design was employed. The participants were 210 Grade 12 students enrolled in TEFA classes within Welding Engineering programs at public and private vocational high schools, selected through proportional random sampling. Path analysis based on multiple regression was used to test the proposed relationships. TEFA engagement (β = .360, p < .001), entrepreneurial knowledge (β = .115, p = .023), and social relationships (β = .410, p < .001) were positively associated with self-efficacy and jointly explained 54.4% of its variance. TEFA engagement (β = .162, p = .005), entrepreneurial knowledge (β = .187, p < .001), social relationships (β = .126, p = .037), and self-efficacy (β = .499, p < .001) were positively associated with entrepreneurial mindset and jointly explained 63.6% of its variance. Social relationships were the strongest predictor of self-efficacy, whereas self-efficacy was the strongest predictor of entrepreneurial mindset. These findings indicate that TEFA programs should integrate authentic production activities, practical entrepreneurship instruction, and sustained support from teachers, peers, and industry professionals to strengthen students’ confidence and entrepreneurial orientation. Because indirect effects were not formally tested, the results should not be interpreted as evidence of statistical mediation or definitive causality.